Peran Menu dan Layanan Makanan dalam Menarik Pelanggan di Coffee Shop di Arsa Coffee & Library - Juni Trimo Legowo; Jumaidin Jumaidin (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to analyze the role of the menu and food services in attracting customers at Arsa Coffee & Library, a coffee shop that also functions as a reading space. The research adopts a qualitative approach, utilizing in-depth interviews with customers and management, as well as direct observation of the service process and the menu variety offered. The findings show that unique and high-quality menu options, along with friendly and efficient service, play a significant role in attracting customers to visit this coffee shop. Furthermore, a comfortable atmosphere and food services tailored to customer preferences enhance the overall experience, which in turn strengthens customer loyalty. The study concludes that an innovative menu and optimal service are crucial factors in improving customer appeal and satisfaction at Arsa Coffee & Library.